IMPLEMENTASI TUGAS PRAKTIK BISNIS PADA MATAKULIAH KEWIRAUSAHAAN DALAM MENUMBUHKAN MINAT MAHASISWA MENJADI INTREPRENEUR - Muhammad Iqbal Sayuti Harahap; Zuhrinal M Nawawi (Pusat Riset dan Inovasi Nasional, 2022)
This research focuses on the implementation of business practice assignments in entrepreneurship courses in fostering student interest in becoming entrepreneurs, the purpose of this research is to find out whether entrepreneurship courses, especially in business practices, can provide motivation and interest in entrepreneurship in febi uinsu students. This research is a qualitative research descriptive. Source of data consists of primary and secondary data. Primary data comes from interviews and observations on students. The results of the study stated that 8 out of 10 students could be motivated and foster student interest in becoming interpreneurs, besides that the faculty's strategy was successful in providing these courses because it was also the hope of graduates from the faculty to become entrepreneurs with an entrepreneurial spirit.